Japanese encephalitis virus infection induces mitochondrial-mediated apoptosis through the proapoptotic protein BAX - Yang, Ke; Li, Xinran; Yang, Shuqing; Zheng, Yi; Cao, Sanjie; Yan, Qigui; Huang, Xiaobo; Wen, Yiping; Zhao, Qin; Du, Senyan; Lang, Yifei; Zhao, Shan; et al. (Frontiers in Microbiology, 2024)
Abstract：Japanese encephalitis virus (JEV), a zoonotic flavivirus, is the primary cause of viral encephalitis in Asia. JEV induces apoptosis in a variety of cells. Nevertheless, the precise mechanism underlying apoptosis induced by JEV infection remains to be elucidated. Our previous studies showed that the pro-apoptosis gene BAX may have a role in JEV proliferation. In this study, we constructed a PK-15 cell line (BAX.KO) with BAX gene knockout by CRISPR/Cas9.BAX gene knockout effectively inhibits the proliferation of JEV, Viral protein levels decreased by 39.9%,whereas BAX overexpression has the opposite effect. We confirmed that JEV could induce the apoptosis of PK-15 by DAPI staining and Annexin V-FITC/PI staining.Furthermore, we found that the phosphorylation of P53 and the expression levels of BAX, NOXA, PUMA, and cleaved-caspase-3/9 were significantly upregulated after JEV infection. Moreover, we found that JEV infection not only caused mitochondrial damage, the release of mitochondrial cytochrome C (Cyt C), and the downregulation of the apoptosisinhibiting protein BCL-2 but also reduced the mitochondrial membrane potential (MOMP) and the accumulation of intracellular reactive oxygen species (ROS). These factors collectively encourage the activation of the mitochondrial apoptosis pathway. In contrast, BAX gene knockout significantly reduces the apoptotic changes caused by JEV infection. Treatment with the caspase3 inhibitor attenuated JEV-induced viral proliferation and release, and the viral protein levels of PK-15 and BAX.KO cells were reduced by 46% and 30%, respectively. In conclusion, this study clarified the molecular mechanism of JEV-induced apoptosis and provided a theoretical basis for revealing the pathogenic mechanism of JEV infection.